Social cognitive theory to assess the intention to participate in the facebook metaverse by citizens in Peru during the COVID-19 pandemic - Aldo Alvarez-Risco; Shyla Del-Aguila-Arcentales; Marc Rosen; Jaime A. Ya\~nez (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The current study aims to validate and apply an instrument to assess the relationship between institutional support, technological literacy, and self-efficacy on the intention to participate in the Facebook Metaverse using social cognitive theory. We performed a cross-sectional, analytical study of 410 citizens in Peru to assess the influence of institutional support, technological literacy, and self-efficacy on the intention to participate in the Facebook Metaverse during the COVID-19 pandemic. The research model was validated using partial least square structural equation modeling (PLS-SEM) to establish the influence of variables on the model. Institutional support and technological literacy were found to influence the self-efficacy of participating in the metaverse positively by correlations of 0.573 and 0.257, respectively. Self-efficacy of participating positively influenced the intention to participate in the Facebook Metaverse by 0.808. The model explained 65.4% of the intention to participate in the Facebook Metaverse. Bootstrapping demonstrated that the path coefficients of the research model were statistically significant. The research outcomes may help firms to develop planning and investment in the metaverse, as well as understanding the factors that influence a higher intention to participate in the Facebook Metaverse.
Keywords: 650; COVID-19; self-efficacy; technology; Facebook; institutional support; intention to participate; metaverse; Peru